2017
DOI: 10.1080/14728214.2017.1293649
|View full text |Cite
|
Sign up to set email alerts
|

Emerging antibodies for the treatment of pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma cancer (PDAC) is the fourth leading cause of cancer death worldwide. Recently, two chemotherapy regimens have proven to improve median overall survival in comparison with gemcitabine. Based on better understanding of tumor molecular biology and of the role of tumor microenvironment, monoclonal antibodies (mAbs) could be an interesting and new type of targeted treatment of PDAC. Areas covered: Preclinical and clinical trials have evaluated the efficacy of several mAbs in pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…In pancreatic cancer, vascular endothelial growth factor receptor (VEGFR), epidermal growth factor receptor (EGFR), insulin-like growth factor 1 receptor (IGF1R) or matrix metalloproteinases (MMPs), such as MMP-9, are commonly overexpressed, which allows treatment of pancreatic cancer using certain small molecule inhibitors against these proteins (22,23). Dasatinib is a potent receptor tyrosine kinase/Src inhibitor, which reduces pancreatic tumor cell growth in vitro (11).…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic cancer, vascular endothelial growth factor receptor (VEGFR), epidermal growth factor receptor (EGFR), insulin-like growth factor 1 receptor (IGF1R) or matrix metalloproteinases (MMPs), such as MMP-9, are commonly overexpressed, which allows treatment of pancreatic cancer using certain small molecule inhibitors against these proteins (22,23). Dasatinib is a potent receptor tyrosine kinase/Src inhibitor, which reduces pancreatic tumor cell growth in vitro (11).…”
Section: Discussionmentioning
confidence: 99%
“…Disappointingly, singleagent immunotherapy has had little effect in PDAC [54]. Increasing evidence suggests that the PDAC microenvironment is comprised of an intricate network of signals between immune cells, PDAC cells and stroma, resulting in an immunosuppressive environment resistant to single-agent immunotherapies [54,55]. It has also been shown that a higher density of CD3+ T-cells in the stroma is associated with longer progression-free survival in patients with PDAC [56], and that combination of mutational profiles and immune markers may define subgroups of patients who may respond to specific types of therapies [57].…”
Section: Immunotherapymentioning
confidence: 99%
“…By inhibiting inflammationpromoted cancer progression, the JAK-STAT inhibitor ruxolitinib achieved promising outcomes in preclinical and phase II trials ( 65), but the subsequent phase III trial was terminated prematurely after demonstration of insufficient efficacy at a planned interim analysis of the JANUS1 trial. Additional strategies involved inhibitors of EGFR, HER2, IGF-1, VEGF, NOTCH, WNT and farnesyl-transferase pathways mainly in combination with gemcitabine (66). Early trials indicate that patients carrying BRCA mutations may benefit from platinum agents and PARP inhibitors.…”
Section: Targeted Agentsmentioning
confidence: 99%